The National Health Service - Great Britain. Central Office of Information. (London : His Majesty's Stationery Office, 1948)
1948 1948 1940s 38 pages most of the ordinary needs of a district (such as a town and the country areas around it, or a group of neighbouring towns with the country in between). Each of these hospital-service units has a single management committee, but there is no standardised pattern. In the large cities the hospitals are sometimes divided between two or three committees ; elsewhere there is only one. Some large single hospitals have management committees of their own. The hospital-groups vary very much in size according to local conditions, and some groups are confined to hospitals of a special kind instead of being 'all-purpose' units. In most of the groups certain hospitals have a house committee with delegated powers appointed by the management committee. In their membership the management committees have been designed to reflect the communities they serve, the doctors and authorities of those communities, and the professions actually working in the hospitals. Each has members appointed after consultation with the Local Health Authority, the Executive Council responsible for the family doctor service, and the senior doctors and dentists working in the hospitals, all of whom must — under the Act — be consulted by the regional boards in making the appointments. They include many of the men and women who managed the same hospitals when they were under voluntary or local authority control, with many more recommended by interested bodies of local citizens, such as Women's Institutes, Trades Councils, and social service organisations. Formerly in many municipal hospitals the chief officer or 'medical superintendent' managed both the business and the medical arrangements. He might or might not treat patients himself, but he sometimes had some control over the way in which the other doctors cared for their patients, and those doctors were mostly employed full-time in one hospital. This limited both the responsibility and the medical experience of the doctors, and, because the medical superintendent was paid more than they, offered the best posts to men who gave up medicine for management. The tendency is likely to be to change this arrangement to something nearer that of the former voluntary hospitals. That is to say the hospital manager, whether doctor or layman, will be a business manager. Medical matters will be in the hands of a committee of the senior medical staff working closely with the hospital management committee, and being consulted on everything affecting their professional work. While junior doctors will commonly continue to work full-time in one hospital, most of the senior doctors will serve several hospitals, giving part of their time to each ; this is the best way for them to spread, and to improve still further, their own skill and experience. The formation of representative committees of nurses and other sections of hospital staffs is also being encouraged, so that all who work in hospitals may have a proper voice in their daily management. 12 21/1489